Investigating the Potential of Lepidium sativum Seed Mucilage as Binder in Tablet Formulation - Shinde, Yogita; Deokar, Gitanjali (International Journal of Pharmaceutical Investigation, 2025)
Introduction The demand for natural excipients in pharmaceuticals has driven interest in plant-based materials. Lepidium sativum seed mucilage, a polysaccharide-rich and biocompatible compound, shows promise as a tablet binder for controlled drug delivery. This study evaluates its potential and optimization in tablet formulations. Objectives This study aimed to assess Lepidium sativum seed mucilage as a natural binder, optimizing tablet formulations for pre- and post-compression parameters, drug release behavior, and release mechanisms. Materials and Methods Mucilage was extracted and confirmed via FTIR spectroscopy. A Central Composite Design (CCD) optimized formulations based on pre-compression (bulk density, tapped density, angle of repose) and post-compression (hardness, friability, disintegration, drug content) parameters. In vitro dissolution studies assessed drug release, while kinetic modeling identified release mechanisms. Results Batch F8 exhibited superior flow properties, uniformity, and high drug content. It’s in vitro dissolution study showed 95.46% drug release over 12 hr, outperforming other formulations. Kinetic analysis confirmed a Higuchi model release, indicating diffusion-controlled drug release. Stability studies confirmed the robustness of the optimized formulation, establishing the potential of Lepidium sativum mucilage as a scalable, natural excipient for pharmaceutical applications. Conclusion Lepidium sativum seed mucilage demonstrated excellent binding properties, supporting its role as a natural excipient for controlled drug delivery. Its potential for scalability and stability warrants further investigation.
Keywords: Lepidium sativum; Mucilage; QbD; DOE; Controlled Drug Delivery